2021
DOI: 10.1007/978-3-030-81341-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Sexual and Gender Politics: Projects and Narratives of Russia’s Far Right

Abstract: The creation and entrenchment of heteronormative gender norms are a core project of the contemporary Russian far right, and in recent years, it has been accompanied by a reduction in legal protections and rising violence against those who do not conform to such norms (Kondakov 2019). All of these efforts are carried out by a network of institutions and individuals originating from the State (here defined as the nation's governing body, its various Ministries, and central individuals such as President Vladimir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In particular, pioneering research by Stoeckl has shown close cooperation of actors in Russia with international and transnational conservative networks (2020). Much attention in connection to the distribution of "traditional values" was received by the Russian Orthodox Church (hereafter, ROC), which is often given the central place with regard to the distribution of "traditional values" (Bluhm and Brand, 2018;Krafft, 2022) For example, "traditional values" are often used by Putin in di erent contexts (Johnson et al, ).…”
Section: Omsk Meat Processing Plant-made In Russiamentioning
confidence: 99%
“…In particular, pioneering research by Stoeckl has shown close cooperation of actors in Russia with international and transnational conservative networks (2020). Much attention in connection to the distribution of "traditional values" was received by the Russian Orthodox Church (hereafter, ROC), which is often given the central place with regard to the distribution of "traditional values" (Bluhm and Brand, 2018;Krafft, 2022) For example, "traditional values" are often used by Putin in di erent contexts (Johnson et al, ).…”
Section: Omsk Meat Processing Plant-made In Russiamentioning
confidence: 99%